ANALISIS TINGKAT LABOUR UTILITATION RATE (LUR) PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAAN PASANGAN BATA PEMBANGUNAN GIS 150 kV KOTA PADANG - Honesti, Leli; Yusnita, Yessy (Ensiklopedia of Journal, 2022)
One of the elements that affect the achievement of construction project objectives is labor productivity. The level of labor productivity can be measured in various ways, where one method that is already known is the Labor Utilization Rate (LUR) method. Here it is assessed how much the LUR level of each worker is, namely the level of effectiveness of workers at work. Several factors that can affect the level of productivity, in this case are age, work experience, education level, wage suitability, health, relations between workers, and managerial. The purpose of this research is to 1). determine the level of Labor Utilization Rate (LUR) of labor productivity; 2). determine the factors that influence age, work experience, education level, wage suitability, health, relations between workers, and managerial on labor productivity and, 3) determine which factors are the most dominant influencing productivity levels in bricklaying work. The research was conducted at the 150 kV GIS construction project in Padang City by observing the productivity level of each 10 workers for 3 days and accompanied by filling out a questionnaire. Based on observations in the field, then taking and collecting data, namely productivity data and questionnaires, then data processing was carried out with the help of the SPSS version 21 program. the 150 kV GIS development project in Padang City is 89.29% > 50%. This shows productive because it is more than 50%. Variables that have been determined, with a significance value of 0.053 > 0.05, so that it simultaneously has no effect. Then, partially age with a sig value of 0.011 <0.05 and work experience with a sig of 0.041 <0.05, so that it affects the level of productivity. From this study also found that managerial variables have an effect, which is the most dominant, which has a beta value of 1.953.